Magnetospheric Multiscale Observations of Waves and Parallel Electric Fields in Reconnecting Current Sheets in the Turbulent Magnetosheath. Issue 9 (25th September 2022) - Wilder, F. D.; Conley, M.; Ergun, R. E.; Newman, D. L.; Chasapis, A.; Ahmadi, N.; Burch, J. L.; Torbert, R. B.; Strangeway, R. J.; Giles, B. L.; Le Contel, O.
Abstract: Downstream of the Earth's bow shock, the magnetosheath can exhibit strong turbulence. This turbulent cascade is associated with electron‐scale current sheets where magnetic reconnection can occur. We present data from NASA's Magnetospheric Multiscale mission during a turbulent magnetosheath interval that includes two electron‐scale reconnecting current sheets, one with higher guide field and one that is closer to antiparallel. We examine the characteristics of energy conversion and the role of parallel electric fields and waves in that energy conversion. The high‐guide field reconnection event shows energy conversion dominated by electric fields and currents parallel to the background magnetic field, while the lower guide field event is perpendicular dominated, consistent with observations of laminar reconnecting current sheets in the magnetosheath. Both current sheets exhibit signs of a parallel electric field acceleration channel, and the higher guide field event shows whistler‐mode waves at the x ‐line. Both current sheets show variation in dissipation along the n‐direction, with perpendicular dissipation on one side and parallel on the other. Between the two is a dispersion of pitch angles from 90° to 0° or 180°. This dispersion is likely caused by the acceleration channel and rapidly suppresses whistler waves, suggesting whistler waves do not contribute to the dissipation in guide field reconnection. Key Points: Two magnetic reconnection events are observed in the turbulent magnetosheath with different guide field Both current sheets exhibit a parallel electric field acceleration channel that changes the anisotropy of the electrons This acceleration channel is sufficient to suppress whistler waves near the diffusion region